Improving School Attendance through Collaboration: A Catalyst for Community Involvement and Change. Issue 1 (3rd April 2018) - Childs, Joshua; Grooms, Ain A.
ABSTRACT: Chronic absenteeism is often referred to as a problem hidden in plain sight (Chang & Romero, 2008). In recent years, more communities around the United States have been intentional on improving student attendance and limiting the impact of chronic absenteeism. Using qualitative interviews, we sought to understand how one community was implementing strategies to engage a variety of stakeholders in an effort to decrease chronic absenteeism. Findings suggest that when it comes to increasing attendance, districts and schools should consider partnering with organizations to leverage their expertise and knowledge. This article concludes with implications for policy and practice, and concludes with a research framework for studying solutions and interventions around chronic absenteeism.